2006
DOI: 10.1055/s-2006-956238
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Gene Expression in Skin Flaps with Arterial and Venous Ischemia in Rats

Abstract: Infiltration of inflammatory cells is the crucial element in ischemia-reperfusion injury of the microsurgical flap. Cytokines are a large functional group of polypeptide regulatory molecules that influence the activity of various cell types through autocrine and paracrine mechanisms. In this study, expression of selected proinflammatory cytokines was examined in skin flaps with arterial and venous ischemia in the rat model. Fifty-four Sprague-Dawley rats were used in the study. The ischemia of each flap was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…112 Subcutaneous VEGF injection into rat dorsal flaps before elevation significantly decreased expression of TNF-α, a cytokine implicated in tissue injury associated with reperfusion. 118,119 VEGF Gene Therapy VEGF availability to the flap site is poorly sustained due to its short half-life. Gene therapy is an attractive option for potential treatment of nonhealing wounds.…”
Section: Pathway Of Vegf Cascadementioning
confidence: 99%
“…112 Subcutaneous VEGF injection into rat dorsal flaps before elevation significantly decreased expression of TNF-α, a cytokine implicated in tissue injury associated with reperfusion. 118,119 VEGF Gene Therapy VEGF availability to the flap site is poorly sustained due to its short half-life. Gene therapy is an attractive option for potential treatment of nonhealing wounds.…”
Section: Pathway Of Vegf Cascadementioning
confidence: 99%
“…The activation and recruitment of PMNs is modulated by many inflammatory mediators. Recent studies have shown that the cascading overexpression of various inflammatory mediator genes, such as tumor necrosis factor-a, interleukin-1b, 9 intercellular adhesion molecule-1, 10 CD18, [11][12][13] and E/L-selectin, 14 may be the underlying molecular mechanism of PMN activation and recruitment in the early reperfusion period. However, it has become evident that these fundamental biological systems are controlled by many interrelated pathways.…”
Section: Figurementioning
confidence: 99%
“…Much research in flap I/R injury has focused on the signaling processes within the immune system that activate PMN, recruit them from the periphery, cause adherence to the endothelium, and stimulate the ''respiratory burst'' or release of cytodestructive agents. 8 Recent studies showed that up-regulated expression of proinflammatory molecules, such as tumor necrosis factor-a and interleukin-1b, 9 intercellular adhesion molecule-1, 10 CD18, [11][12][13] and E/L-selectin, 14 were responsible for the activation and infiltration of PMNs. However, the exact mechanisms responsible for the up-regulation of those mediators have not yet been well defined.…”
mentioning
confidence: 99%
“…Only a limited number of studies have compared transcriptional changes in arterial ischemia and venous congestion. Zhang et al used a skin flap model and found that tumor necrosis factor (TNF-alpha) was significantly up-regulated in arterial ischemia, whereas monocyte chemoattractant protein-1 (MCP-1) was associated with venous congestion [40]. Mithani et al used a rat flap model to identify genes related to flap failure, but only studied venous congestion [41].…”
Section: Introductionmentioning
confidence: 99%